SURFACE URBAN COOL ISLAND ASSESSMENT IN VILLAGE-LEVEL TOURISM DESTINATIONS USING GIS AND PRINCIPAL COMPONENT ANALYSIS - Hernina, Revi; Wicaksono, Arif (Jurnal Geografi Lingkungan Tropik (Journal of Geography of Tropical Environments), 2024)
This study describes the process to generate classification of village-level tourism destinations known as kampung tematik in Bogor Municipality based on values from Surface Urban Cool Island (SUCI), Normalized Difference Built-up Index (NDBI) ≤ -0.17, Normalized Difference Vegetation Index (NDVI) > 0.3, and Urban Index (UI) < -0.2. SUCI values represent the cool temperature, while NDBI ≤ -0.17, NDVI > 0.3, and UI < -0.2 are associated with dense and healthy vegetation. Herein, Band 10 from Landsat 8 was processed to generate land surface temperature (LST) and further, SUCI image was derived from LST image by employing SUCI algorithm. All three variables, namely NDVI, NDBI, and UI were also processed from Landsat 8 with date 24 May 2020. These four variables of SUCI, NDVI, NDBI, and UI image pixels were superimposed with 39 kampung tematik locations using Geographic Information System (GIS) which resulted in 14 locations containing the area percentage from four variables. The values from four variables in 14 locations were inputted into Principal component Analysis (PCA) using R software version 4.1.3. Based on PCA, it reveals that three tourism destinations are classified with area percentage of SUCI less than 50% while the other 11 destinations are classified with area percentage of SUCI more than 50%. In addition, characteristics of tourism destinations with SUCI area percentage less than 50% are identified to have low area percentage of NDBI ≤ -0.17, NDVI > 0.3, and UI < -0.2.